THE INFLUENCE OF STATE CAPITAL PARTICIPATION, STRATEGIC ORIENTATION, AND ACCOUNTABILITY ON THE FINANCIAL PERFORMANCE OF STATE-OWNED ENTERPRISES: A PANEL DATA FEM ANALYSIS (2021–2024) - Annisa, Mutiara; Yanti, Harti Budi (Faculty of Economics and Business, 2025)
This study aims to analyze the influence of State Capital Participation (PMN), strategic orientation, accountability, good corporate governance (GCG), and risk management on the financial performance of State-Owned Enterprises (SOEs) in Indonesia during the 2021–2024 period. Using a quantitative approach with panel data and the Fixed Effect Model (FEM), the research involved 62 SOEs with a total of 217 observations. The results show that, simultaneously, the five independent variables significantly affect financial performance as measured by net profit after tax. However, individually, none of the variables show a statistically significant impact. These findings suggest that PMN and internal strategies have not yet delivered direct short-term improvements in profitability, likely due to external factors such as government intervention, long-term projects, and post-pandemic economic conditions. Furthermore, the implementation of GCG, accountability, and risk management tends to have long-term effects that are not immediately reflected in financial outcomes. This study contributes to the understanding of how structural and strategic factors interact in shaping SOE performance and recommends that policymakers and SOE leaders enhance coordination between fiscal support and internal governance reforms to achieve sustainable financial outcomes.